The Legality and Legibility of Unregistered Marriages in Indonesia: Assessing the Complementarity of the Marriage Law and the Population Administration Law - Vita Fitria; Ali Sodiqin (UIN Sunan Kalijaga Yogyakarta, 2026)
The phenomenon of unregistered marriages in Indonesia persists as a social reality even though it is not legally recognized within the marriage registration system. On the one hand, the Marriage Law establishes registration as a means to ensure legal certainty and protection; on the other hand, the Population Administration Law provides an administrative avenue for those in unregistered marriages by allowing the inclusion of family relationship status on the Family Card. This situation has sparked a debate over whether such administrative policies undermine the principle of the legality of marriage or, conversely, constitute a form of protection for citizens’ civil rights. This study aims to analyze the relationship between the Marriage Law and the Population Administration Law to examine whether the two are contradictory or complementary. This study is a normative legal study employing a legislative and conceptual approach. The data analyzed include the Marriage Law, the Population Administration Law, and Ministry of Home Affairs Regulation No. 108 of 2019. The theoretical framework used consists of legal pluralism, state legibility, and Jasser Auda’s systemic maqasid syariah. The research findings indicate that the regulation of unregistered marriages is based on two orientations: formal legality under the Marriage Law and administrative legibility under the Population Administration Law. These two regulations are not contradictory; rather, they serve distinct yet complementary functions in providing legal and administrative protection. However, the lack of optimal integration between these two legal frameworks has led to the perception that unregistered marriages are legitimate. Therefore, regulatory synchronization is necessary to establish a unified legal system, provide legal certainty, and ensure fair and substantive protection. Fenomena nikah siri di Indonesia tetap bertahan sebagai realitas sosial meskipun tidak memperoleh pengakuan hukum dalam sistem pencatatan perkawinan. Di satu sisi, Undang-Undang Perkawinan menempatkan pencatatan sebagai instrumen untuk menjamin kepastian dan perlindungan hukum, akan tetapi di sisi lain Undang-Undang Administrasi Kependudukan membuka ruang administrasi bagi pelaku nikah siri melalui pencantuman status hubungan keluarga dalam Kartu Keluarga. Kondisi ini memunculkan perdebatan mengenai apakah kebijakan administrasi tersebut melemahkan prinsip legalitas perkawinan atau justru merupakan bentuk perlindungan hak-hak sipil warga negara. Penelitian ini bertujuan menganalisis hubungan antara Undang-Undang Perkawinan dan Undang-Undang Administrasi Kependudukan untuk menguji apakah keduanya bersifat kontradiktif atau komplementer. Penelitian ini merupakan penelitian hukum normatif dengan pendekatan perundang-undangan dan konseptual. Data yang dianalisis adalah Undang-Undang Perkawinan, Undang-Undang Administrasi Kependudukan, dan Permendagri Nomor 108 Tahun 2019. Kerangka teori yang digunakan adalah legal pluralism, state legibility, dan maqasid syariah sistemik Jasser Auda. Hasil penelitian menunjukkan bahwa pengaturan nikah siri dibangun atas dua orientasi, yaitu legalitas formal dalam Undang-Undang Perkawinan dan legibilitas (keterbacaan) administratif dalam Undang-Undang Administrasi Kependudukan. Kedua regulasi tidak bersifat kontradiktif, melainkan menjalankan fungsi yang berbeda namun saling melengkapi dalam memberikan perlindungan hukum dan administratif. Namun, belum optimalnya integrasi kedua regulasi hukum tersebut menimbulkan persepsi adanya legitimasi terhadap nikah siri. Oleh karena itu, diperlukan sinkronisasi regulasi untuk mewujudkan sistem hukum yang terpadu, memberikan kepastian hukum, dan menjamin perlindungan substantif yang berkeadilan.